Analisis Pengukuran Usability Pada Situs Badan Pusat Statistik Provinsi Sumatera Selatan Dengan Menggunakan Metode Webuse - Ali Abdul Jabbar Ibnurozi; Rusmala Santi; Catur Eri Gunawan (APTIKOM SUMSEL, 2020)
The Central Statistics Agency of South Sumatra Province has an official website that provides information about the census. This BPS website can be accessed by users who want to find data about the census. However, this site still has several problems, both in terms of interface appearance and ease of use. This research aims to measure the ease of use of the website of the Central Statistics Agency of South Sumatra Province by conducting a usability test using the Webuse method. This study used a sample of 96 respondents using the Lameshow formula. The data collection method used is by distributing questionnaires both offline and online. The results of this study indicate that each variable has a good usability level. With the content, organization, and readability variables having a value of 0.76, the navigation and links variable having a value of 0.75, the user interface design variable having a value of 0.76, and the performance and effectiveness variable having a value of 0.77. So it can be concluded that the website of the Central Statistics Agency of South Sumatra has a good level of usability according to the results of the study, which obtained data from 96 different respondents as the sample